ASEAN’s Potential Strategy to Deal and Tackle the Problems in the South China Sea - Adhit Prayoga; Jonni Mahroza; Surryanto Djoko Waluyo (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2023)
The strategic values of the South China Sea trigger consequences, which are the emergence of multiple claims to the sovereignty of the area to exploit the strategic values ​​for the national interest. The claims thus construct complex issues in the South China Sea, which involve China’s assertiveness and the internationalization of the South China Sea circumstance, which makes the situation in the region unconducive and hinders the resolution process. The Association of Southeast Asian Nations (ASEAN) must also deal with different views among several member countries regarding the South China Sea dispute. With a security community formed through the ASEAN Political Security Community, ASEAN must be a platform for its member countries to develop and implement strategies to realize common interests, namely order and security. This research explains the potential strategies ASEAN can carry out in solving problems in the South China Sea. This research used qualitative methods, descriptive analysis, and regional security complex theory. This research finds that the strategy that ASEAN can potentially use is to accelerate the formulation of the Code of Conduct (CoC), restore ASEAN identity, and form the ASEAN Navy and the ASEAN Maritime Identification Zone (ASEAN MIZ); thus, ASEAN can comprehensively fulfill a conducive, peaceful, and secure water area. Keywords: ASEAN, stability and security, sovereignty, South China Sea, maritime security, common interests, strategy Nilai strategis yang dimiliki Laut Tiongkok Selatan membawa konsekuensi berupa munculnya klaim tumpang tindih terhadap kedaulatan area tersebut untuk dapat memanfaatkan nilai strategis yang ada demi kepentingan nasional tertentu. Hal ini menimbulkan permasalahan kompleks di Laut Tiongkok Selatan, yang bukan hanya melibatkan asertivitas Tiongkok, tetapi juga Association of Southeast Asian Nations (ASEAN) yang menghadapi perbedaan pandangan di antara beberapa negara anggota yang membuat situasi di wilayah tersebut semakin tidak kondusif dan menghambat proses penyelesaiannya. Dengan komunitas keamanan yang terbentuk melalui ASEAN Political Security Community, ASEAN harus menjadi wadah bagi negara-negara anggotanya untuk menyusun dan melaksanakan strategi yang dapat mewujudkan kepentingan bersama, yaitu keteraturan dan keamanan. Penelitian ini menjelaskan strategi yang dapat dilakukan ASEAN dalam menghadapi dan menyelesaikan permasalahan di Laut Tiongkok Selatan. Penelitian ini dilaksanakan menggunakan metode kualitatif dan analisis deskriptif serta teori Regional Security Complex. Penelitian ini menemukan bahwa strategi yang dapat dimanfaatkan oleh ASEAN adalah mempercepat perumusan Code of Conduct (CoC), mengembalikan identitas ASEAN, dan membentuk ASEAN Navy serta ASEAN Maritime Identification Zone (ASEAN MIZ), sehingga ASEAN secara menyeluruh dapat mewujudkan wilayah perairan yang kondusif, damai, dan aman. Kata-kata Kunci: ASEAN, keteraturan dan keamanan, kedaulatan, Laut Tiongkok Selatan, keamanan maritim, kepentingan bersama, strategi